Soliton in an Inhomogeneous Highly Dispersive Media with Cubic-Quintic-Septic-Nonical Nonlinearity Law - Rajowar, Chakradhar; Sinha, Abhijit (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we have investigated the propagation of solitons in a highly dispersive inhomogeneous medium with Cubic-Quintic-Septic-Nonical nonlinearity terms. Here the exact bright soliton solution is shown with the solitary wave Ansatz solution and expresses the constraint conditions on the physical parameters for the existence of a bright soliton. Furthermore, the expressions for frequency shift and shift of the inverse group velocity of the optical pulse with the coefficients of higher order terms are derived. Also, we have studied experimentally that the simultaneous presence of space-dependent coefficients of higher order nonlinearities at a proper value with dispersions in the solution of the higher order nonlinear Schrödinger equation provides an exact solitary shape that can travel over a long distance without any distortion.